The role of value added across economic sectors in modulating the effects of FDI on TFP and economic growth dynamics - Simplice Asongu; Christelle Meniago; Raufhon Salahodjaev (African Governance and Development Institute (AGDI), 2021)
This study investigates: (i) the effect of foreign direct investment (FDI) on total factor productivity (TFP) and economic growth dynamics, and (ii) the relevance of value added from three economic sectors in modulating the established effect of FDI on TFP and economic growth dynamics. The geographical and temporal scopes are respectively 25 Sub-Saharan African countries and the period 1980-2014. The empirical evidence is based on non-interactive and interactive Generalised Method of Moments. The following main findings are established. First, FDI has a positive effect on GDP growth, GDP per capita and welfare real TFP. Second, the effect of FDI is negative on real GDP and TFP, while the impact is insignificant on real TFP growth and welfare TFP. Third, values added to the three economic sectors largely modulate FDI to produce negative net effects on TFP and growth dynamics. Policy implications are discussed with particular emphasis on the need to complement added value across various economic sectors in order to leverage on the benefits of FDI in TFP and economic growth. To the best of knowledge, this is the first study to assess how value added from various economic sectors affect the relevance of FDI on macroeconomic outcomes.
Keywords: E23; F21; F30; F43; O55; 330; Economic output; total factor productivity; foreign investment; agricultural sector; manufacturing sector; service sector; sub-Saharan Africa